Clinical Course and Long-term Outcome of Adults with Primary Focal Segmental Glomerulosclerosis: A Retrospective Cohort Study (Iranian Journal of Kidney Diseases, 2022)
Introduction. Focal segmental glomerulosclerosis (FSGS) is one of the common causes of end-stage kidney disease (ESKD) in adults with primary glomerular diseases. Information on clinical course and long-term renal outcome of primary FSGS in adults are scanty. We aimed to determine the clinical course and long-term outcome of primary FSGS in a large number of adult patients from a tertiary care kidney center in Pakistan. Methods. A retrospective review of the clinical charts of all adults (≥ 16 years) with a biopsy proven diagnosis of FSGS presenting to Sindh Institute of Urology and Transplantation, Karachi, between January 1995 and December 2017 was carried out. Cases with secondary FSGS were excluded. Relevant data items were retrieved both at baseline and on last follow-up. Results. Among 401 adults with primary FSGS, 144 (35.9%) were followed for a mean duration of 66.6 ± 27.4 months, out of which, 129 (89.5%) were treated with steroids and immunosuppressants. Response to steroids was obtained in 62 (48%) patients, while 67 (52%) showed no response. Among responders, 24/62 (38.7%) relapsed after a mean duration of 24.2 ± 23.2 weeks, who were re-treated with same dose of steroids alone or combined with cyclosporine and all achieved remission. The long-term outcomes were significantly different between steroid responsive and nonresponsive cohorts. None of the patients in steroid responsive group developed ESKD or died, while 7 (10.4%) patients in nonresponsive group developed ESKD and 2 (3%) died. Conclusion. Almost half of adults with primary FSGS achieved sustained remission with steroids and immunosuppressants and consequently exhibited excellent long-term outcome.  DOI: 10.52547/ijkd.6815